Assessing commercially available personal health records for home health - Kneale, Laura; Choi, Yong; Demiris, George (Applied Clinical Informatics, 2016)
Home health nurses and clients experience unmet information needs when transitioning from hospital to home health. Personal health records (PHRs) support consumer-centered information management activities. Previous work has assessed PHRs associated with healthcare providers, but these systems leave home health nurses unable to access necessary information.To evaluate the ability of publically available PHRs to accept, manage, and share information from a home health case study.Two researchers accessed the publically available PHRs on myPHR.com, and attempted to enter, manage, and share the case study data. We qualitatively described the PHR features, and identified gaps between the case study information and PHR functionality.Eighteen PHRs were identified in our initial search. Seven systems met our inclusion criteria, and are included in this review. The PHRs were able to accept basic medical information. Gaps occurred when entering, managing, and/or sharing data from the acute care and home health episodes. The PHRs that were reviewed were unable to effectively manage the case study information. Therefore, increasing consumer health literacy through these systems may be difficult. The PHRs that we reviewed were also unable to electronically share their data.The gap between the existing functionality and the information needs from the case study may make these PHRs difficult to use for home health environments. Additional work is needed to increase the functionality of the PHR systems to better fit the data needs of home health clients.
Keywords: Personal health record; personal health records; home health nursing; qualitative research